Nanofiltration Membranes Formed through Interfacial Polymerization Involving Cycloalkane Amine Monomer and Trimesoyl Chloride Showing Some Tolerance to Chlorine during Dye Desalination - Micah Belle Marie Yap Ang; Yi-Ling Wu; Min-Yi Chu; Ping-Han Wu; Yu-Hsuan Chiao; Jeremiah C. Millare; Shu-Hsien Huang; Hui-An Tsai; Kueir-Rarn Lee (Membranes, 2022)
Wastewater effluents containing high concentrations of dyes are highly toxic to the environment and aquatic organisms. Recycle and reuse of both water and dye in textile industries can save energy and costs. Thus, new materials are being explored to fabricate highly efficient nanofiltration membranes for fulfilling industrial needs. In this work, three diamines, 1,4-cyclohexanediamine (CHD), ethylenediamine (EDA), and p-phenylenediamine (PPD), are reacted with TMC separately to fabricate a thin film composite polyamide membrane for dye desalination. Their chemical structures are different, with the difference located in the middle of two terminal amines. The surface morphology, roughness, and thickness of the polyamide layer are dependent on the reactivity of the diamines with TMC. EDA has a short linear alkane chain, which can easily react with TMC, forming a very dense selective layer. CHD has a cyclohexane ring, making it more sterically hindered than EDA. As such, CHD’s reaction with TMC is slower than EDA’s, leading to a thinner polyamide layer. PPD has a benzene ring, which should make it the most sterically hindered structure; however, its benzene ring has a pi-pi interaction with TMC that can facilitate a faster reaction between PPD and TMC, leading to a thicker polyamide layer. Among the TFC membranes, TFCCHD exhibited the highest separation efficiency (pure water flux = 192.13 ± 7.11 L∙m−2∙h−1, dye rejection = 99.92 ± 0.10%, and NaCl rejection = 15.46 ± 1.68% at 6 bar and 1000 ppm salt or 50 ppm of dye solution). After exposure at 12,000 ppm∙h of active chlorine, the flux of TFCCHD was enhanced with maintained high dye rejection. Therefore, the TFCCHD membrane has a potential application for dye desalination process.